A Structural Competency Curriculum for Primary Care Providers to Address the Opioid Use Disorder, HIV, and Hepatitis C Syndemic - Bagchi, Ann D. (Frontiers in Public Health, 2020)
The interrelated epidemics of opioid use disorder (OUD) and HIV and hepatitis C virus (HCV) infection have been identified as one of the most pressing syndemics facing the United States today. Research studies and interventions have begun to address the structural factors that promote the inter-relations between these conditions and a number of training programs to improve structural awareness have targeted physician trainees (e.g., residents and medical students). However, a significant limitation in these programs is the failure to include practicing primary care providers (PCPs). Over the past five years, there have been increasing calls for PCPs to develop structural competency as a way to provide a more integrated and patient-centered approach to prevention and care in the syndemic. This paper applies Metzel and Hansen’s (2014) framework for improved structural competency to describe an educational curriculum that can be delivered to practicing PCPs. Skill 1 involves reviewing the historical precedents (particularly stigma) that created the siloed systems of care for OUD, HIV, and HCV and examines how recent biomedical advances allow for greater care integration. To help clinicians develop a more multidisciplinary understanding of structure (Skill 2), trainees will discuss ways to assess structural vulnerability. Next, providers will review case studies to better understand how structural foundations are usually seen as cultural representations (Skill 3). Developing structural interventions (Skill 4) involves identifying ways to create a more integrated system of care that can overcome clinical inertia. Finally, the training will emphasize cultural humility (Skill 5) through empathetic and non-judgmental patient interactions. Demonstrating understanding of the structural barriers that patients face is expected to enhance patient trust and increase retention in care. The immediate objective is to pilot test the feasibility of the curriculum in a small sample of primary care sites and develop metrics for future evaluation. While the short-term goal is to test the model among practicing PCPs, the long-term goal is to implement the training practice-wide to ensure structural competence throughout the clinical setting.